2014
DOI: 10.1016/j.jacc.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Headed in the Right Direction But at Risk for Miscalculation

Abstract: The newly released 2013 ACC/AHA Guidelines for Assessing Cardiovascular Risk makes progress compared with previous cardiovascular risk assessment algorithms. For example, the new focus on total atherosclerotic cardiovascular diseases (ASCVD) is now inclusive of stroke in addition to hard coronary events, and there are now separate equations to facilitate estimation of risk in non-Hispanic white and black individuals and separate equations for women. Physicians may now estimate lifetime risk in addition to 10-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…In sum, as recently recommended (27), we conducted a critical evaluation of the ASCVD Pooled Cohort risk equation from a relevant large, diverse, “real-world” target population, overall and in key understudied subgroups. We found that this risk equation substantially overestimated actual ASCVD risk in adults not treated with statin therapy for primary prevention without diabetes (overall and across all sociodemographic subgroups), and demonstrated suboptimal accuracy in those with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, as recently recommended (27), we conducted a critical evaluation of the ASCVD Pooled Cohort risk equation from a relevant large, diverse, “real-world” target population, overall and in key understudied subgroups. We found that this risk equation substantially overestimated actual ASCVD risk in adults not treated with statin therapy for primary prevention without diabetes (overall and across all sociodemographic subgroups), and demonstrated suboptimal accuracy in those with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…19 Differences in socioeconomic status and secular trends of CVD risk factors not captured in risk scores, along with changing incidence patterns of CVD and overall health between the cohorts used for developing the Pooled Cohort Equations and modern populations, may explain this phenomenon. 6 Further research in this area will enhance our understanding regarding the reasons for such overestimation.…”
Section: Approach To Global Risk Assessment: Old Paradigms Modern Prmentioning
confidence: 99%
“…In 2011, DeFilippis et al demonstrated a 40% higher risk of incident CAC per 5% higher absolute FRS risk, and a mean 7 Agatston score increase per 5% higher FRS among those with existing CAC. 15 However given concerns about possible limitations of the FRS, 16 including lack of race and ethnic diversity in the derivation sample and the absence of certain newly identified risk factors, competing risk scores including the Reynolds Risk Score (RRS) were also studied. The 2008 RRS added family history and high sensitivity C-reactive protein (hsCRP) to the risk algorithm along with the traditional Framingham risk factors.…”
Section: Introductionmentioning
confidence: 99%